Cross-taxon congruence between predatory arthropods and plants across Mediterranean agricultural landscapes - Daria Corcos (Elsevier, 2021)
Although arthropods are among the most diverse, abundant and ecologically important animals in terrestrial ecosystems, they are generally neglected in most biodiversity inventories due to their complex systematics and overwhelming diversity, coupled with the current decline in the number of taxonomists. For this reason, several surrogate groups for arthropod diversity have been proposed, with plants being identified as a good putative cross-taxon indicator. By sampling plants and three groups of ground-dwelling arthropods (rove beetles, ground beetles and spiders) in 300 sites across 15 landscapes including multiple semi-natural and agricultural habitats, we tested for habitat-dependence and scale-dependence in the cross-taxon congruence. Plant species richness was a poor predictor of the species richness of predatory arthropods. Among the predator groups, ground beetles appeared as the best potential surrogate for the other ground-dwelling predators. This is backed by the fact that ground beetles were extremely diverse and abundant in all habitats and are usually easier to identify than both rove beetles and spiders. Decreasing the scale at which the cross-taxon congruence was tested improved the strength of the cross-taxon congruence. Although plant species richness was not a suitable indicator for the diversity of predatory arthropods, vegetation structure played a significant role in influencing cross-taxon congruence in both natural and agricultural habitats. Our results highlight the need to explore the cross-taxon relationships at a fine habitat resolution scale, as strong correlations were obtained only by taking into account habitat identity.